Pengembangan media flash card berbasis make a match pada materi wujud zat dan perubahannya kelas IV SD - Della Ariani; Lukman Hakim; Lefudin (COLLASE (Creative of Learning Students Elementary Education), 2026)
This research and development aimed to produce a make a match-based flash card learning media that is valid, practical, and effective for use in fourth-grade IPAS learning. The study was prompted by a needs analysis which revealed that most fourth-grade students at SD Negeri 27 Palembang were not accustomed to using interactive learning media such as flash cards and experienced difficulties in understanding IPAS material, particularly the topic of states of matter and their changes. Furthermore, student participation in learning activities was generally low. The development process followed the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. Data were collected through expert validation, student response questionnaires, and learning outcome tests. Validation by three experts resulted in an average score of 92.5%, indicating high validity. Practicality testing through one-to-one and small group assessments yielded scores of 97.3% and 96.8%, respectively, categorized as highly practical. Effectiveness testing showed an N-Gain score of 0.77, indicating a high level of effectiveness. Therefore, the make a match-based flash card media is considered suitable for enhancing students’ conceptual understanding and engagement in IPAS learning for fourth-grade students.